Bridging FSAS and FASB: A Theoretical and Practical Clash of Accounting Standards - Bratakusuma, Sumantri; Tajuroh Afiah, Efi (Advances in Accounting Innovation, 2025)
Objective: The objective of this research is to contrast the practical and theoretical consequences of the implementation of an accounting standard between FSAS and FASB, with the emphasis on how the alignment of theory and professional judgment affects quality financial reporting.Methods: I used a theory-themed perspective and used the validated measures to investigate the influence of accounting standards on the quality of reporting by employing EFA and SPSS regression approaches.Results: The findings indicate two main points. First, both FSAS and FASB affect financial reporting quality. Second, FSAS is more contextually embedded with environmental regulatory and institutional forces in Indonesia. The theoretical fit and professional belief were identified as mediators in the standards to reporting relationship. Respondents who demonstrated a high degree of theoretical fit and exhibited above-average ethical judgment exhibited superior performance with regard to relevance, timeliness, and report completeness.Novelty: This study is pioneering in its integration of accounting theory, cross-standard (FSAS vs. FASB) comparison, and behavioral (judgment) dimensions within a unified framework. It offers a novel approach to understanding the impact of local context and theoretical adherence on accounting practice.Research Implications: The results have important implications both for the policy-makers and for the educators of accountants in relation to the necessity to embed in accounting education and accountancy setting, the ability to reason theoretically and make ethical judgments. The study provides practitioners with practical implications on how theoretical knowledge can increase the quality of compliance and reporting as well as to contribute to globally convergence not merely technical standardization.